Rehabilitation of abandoned housing projects of liquidated housing-developer-companies: a comparative legal analysis between the position in Malaysia and in The United Kingdom - Md Dahlan, Nuarrual Hilal; Syed Abdul Kader, Sharifah Zubaidah (LexisNexis, 2012)
Although the Malaysian government has enacted law and formulated policies to govern the housing industry since it achieved Independence in 1957, abandoned housing projects remain a recurrent problem until today. The real victims are the purchasers themselves. When a housing developer company is wound up, the affair and business of the company of the company are taken over either by the private liquidator or provisional liquidator or the official receiver ('OR') under the Department of Insolvency. The liquidator may rehabilitate the abandoned projects left by the wound up housing developer companies, if the projects are viable for rehabilitation with the approval of the creditors, contributories, the committee of inspection and the court and where there are adequate funds to finance the rehabilitation. Otherwise, if the project is not viable, particularly because there are insufficient funds to run the rehabilitation or the problems of the abandoned housing projects are to complicated, the projects may be stalled forever without any prospects for rehabilitation, to the detriment of the purchaser. The position in the United Kingdom ('UK') in respect of similar issues is also comparatively analysed. At the end of this paper, the authors propose certain suggestions in facing the problems of abandoned housing projects of wound up housing developer companies and rehabilitation in Malaysia and in the United Kingdom.